Trends in tobacco smoking among Czech School-aged Children from 1994 to 2014 - Salonna, Ferdinand; Kážmér, Ladislav; Csémy, Ladislav; Vašíčková, Jana; Hublet, Anne; Stock, Christiane (Central European Journal of Public Health, 2017)
OBJECTIVE: The aim of the article is to examine trends in tobacco consumption among the Czech school-age population. METHODS: For the analysis, data from the Czech Health Behaviour in School-aged Children project, conducted between 1994 and 2014 were used. Trends in tobacco smoking were determined separately for boys and girls, applying the binary logistic regression with survey period as an independent variable for the smoking status. RESULTS: The analysis showed that there have been significant changes in adolescent tobacco smoking for the recent 20 years. While the share of current school-aged smokers was continuously increasing since the mid-1990s, the trend reached its peak in the mid-2000s. CONCLUSION: In recent years, the prevalence of adolescent smokers has significantly declined in the Czech Republic. Despite this recent decline, adolescent smoking remains a major challenge for the national health policy.
Keywords: Adolescent; prevalence; kouření; mužské pohlaví; longitudinální studie; zdravé chování; Cross-Sectional Studies; Humans; Child; zdravotnické přehledy; lidé; Health Surveys; Health Behavior; Prevalence; Czech Republic; Smoking; mladiství; Female; Longitudinal Studies; Česká republika; ženské pohlaví; Male; průřezové studie; dítě